Homonyms of Art Terms on the MoMA Official Website - Haerunnisa, Alfiani; EF, Abd. Hanan; Saehu, Andang (Institut Agama Islam Negeri Palopo, 2024)
In the study of language, every word has its own meaning, and occasionally the same word has different meanings that can lead to ambiguity and potential misinterpretation. This is especially true in art terms, where certain terminology may only be understood by artists and people with knowledge of art. The reserch aims to identify art terms sourced from the MoMA official website that fall into the category of homonyms either homographs or homophones, and to explain the differences in meaning of these terms in the context of art and in the general context. The research method uses a qualitative method, with content analysis design. Qualitative Content Analysis in research aims to understand the meaning, theme, or pattern in text data in depth and contextually. Qualitative content analysis in this study emphasizes understanding the context and nuances of meaning, identifying and categorizing art terms that are included in homonyms, such as homographs and homophones, and analyzing their contextual meaning in art and in general meaning. The result of this study is that there are homonyms in art terms sourced from the MoMA official website. Of the 10 data analyzed, there are homonyms including homographs and no homophones were found. Of the ten art terms whose homonyms have been explained, this will reduce errors in interpretation of words that contain meaning in art terms and their general meaning.